The Role Of Chatbots In Reducing Loneliness Among Young Adults: A Descriptive Literature Review - Chionia Karitas (proceedings.icesy, 2026)
This study examined the role of chatbot as a technology which addresses loneliness among adults in the context of mental health. Loneliness has become a growing psychosocial problem associated with varied negative outcomes, both psychologically and physically, particularly among adults experiencing social isolation. This research aimed to explore both the potential benefits and risks of chatbot usage in reducing perceived loneliness and supporting young adults’ mental well-being. A descriptive literature review method was employed and relevant articles were systematically identified from reputable and distinguished academic databases. Predefined keywords were used to identify the articles related to chatbots, artificial intelligence, and loneliness. A total of 1,658 articles were screened, resulting in four literatures that met the inclusion criteria and were analysed in depth. The findings indicated that chatbots contributed positively by providing emotional support, enhancing social presence, improving access to mental health assessment, and reducing perceived loneliness, specifically among socially isolated adults. However, excessive reliance on chatbots was associated with potential risks such as social disengagement, emotional overattachment, limited emotional understanding, and concerns regarding data privacy. In conclusion, chatbot-based technology demonstrated significant potential as a support for mental health tools, but the implementation should be carefully designed with personalisation, ethical considerations, and user safety to ensure sustainable psychological benefits.